Sensors: Electrolyte‐Gated Organic Field‐Effect Transistor Sensors Based on Supported Biotinylated Phospholipid Bilayer (Adv. Mater. 14/2013). (8th April 2013) - Magliulo, Maria; Mallardi, Antonia; Mulla, Mohammad Yusuf; Cotrone, Serafina; Pistillo, Bianca Rita; Favia, Pietro; Vikholm‐Lundin, Inger; Palazzo, Gerardo; Torsi, Luisa
<x xml:space="preserve">Abstract</x> An electrolyte gated organic field‐effect transistor (EGOFET) endowed with a biological capturing layer can allow high performance electronic biodetection in a high ionic strength buffer solution as reported by Luisa Torsi, Gerardo Palazzo and co‐workers on page 2090. The cover image illustrates flexible electronic circuits printed on a protein strand, imaginatively featuring the ultimate integration of the two systems. Image: Daniele Romeo. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>